A CLÁUSULA DEMURRAGE DE CONTÊINER E O PROJETO DE LEI Nº 487/2013: AS (IR)RACIONALIDADES DA PROPOSTA DE REFORMA DO CÓDIGO COMERCIAL - SILVA, Rodrigo Dutra da (2022)
This study aims to understand the legal discipline of container demurrage charges in the framework of maritime transport contracts, especially in the context of importing cargo to Brazil and taking into account the propositions of Federal Bill nº 487/2013. The general objective is to analyze the operational aptitude of the proposed law in order to adequately solve, considering the discussions undertaken on the subject, any regulatory inconsistencies that occur in commercial practice to ensure security, stability and confidence in the business relations of private law, while also conjecture potential effects of the bill in the normative and jurisprudential spheres. The specific objectives are: a) present the system of law in its operational, structural and functional conjunctures to understand the role of private law legislation; b) understand the structuring rationalities of the bill studied, as well as the regulation and operationalization of the maritime transport contract; c) critically analyze the forecasts concerning the container demurrage clause, proposing a legal model to the issue. To this end, it will use the method of pragmatic systemic approach, from a legal-operational perspective, based on the theoretical framework of Niklas Luhmann's theory of autopoietic systems, according to the viewpoint of the work "The law of society" (LUHMANN, 2016). This is a qualitative, monographic, legal-propositional research whose reasoning is structured by the hypothetical-deductive method. In the end, in view of the structure and function of container demurrage charges, it is concluded that, despite intending to conclude all the legal regulation of private law, the proposed law assessed is partially unfeasible to discipline the subject, since relevant conflicting issues were not assessed or were deficiently evaluated, with the potential of resulting in inconsistent or inadequate solutions within the legal system.